2016
DOI: 10.1016/j.future.2015.09.031
|View full text |Cite
|
Sign up to set email alerts
|

Cloud computing adoption framework: A security framework for business clouds

Abstract: This paper presents a Cloud Computing Adoption Framework (CCAF) security suitable for business clouds. CCAF multi-layered security is based on the development and integration of three major security technologies: firewall, identity management and encryption based on the development of Enterprise File Sync and Share technologies. This paper presents our motivation, related work and our views on security framework. Core technologies have been explained in details and experiments were designed to demonstrate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 265 publications
(105 citation statements)
references
References 16 publications
0
100
0
1
Order By: Relevance
“…A multi-layered security solution can reduce the risk of unauthorized access and the use of back-end non-SQL databases should be implemented in core servers/clusters for IoT and BD architectures (Chang et al, 2016). NovaGenesis self-verifying names, pub/sub, and contract-based operation enhances security, privacy, and trust.…”
Section: Discussionmentioning
confidence: 99%
“…A multi-layered security solution can reduce the risk of unauthorized access and the use of back-end non-SQL databases should be implemented in core servers/clusters for IoT and BD architectures (Chang et al, 2016). NovaGenesis self-verifying names, pub/sub, and contract-based operation enhances security, privacy, and trust.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-layered security proposed by Chang et al [54] has demonstrated that penetration testing and ethical hacking of injecting 10,000 known viruses and Trojans in 2013 can be blocked and isolated, with 99.9% success rate. Multi-layered security can be blended with ADLS as an emerging IoT service to ensure that hacking by malicious files injections can be minimized.…”
Section: Extension Of Our Workmentioning
confidence: 99%
“…The method selectively encodes information using privacy classification methods under timing constraints. Besides that, other research studies [14][15][16][17][18][19][20][21][22][23][24] have also considered big data security aspects and solutions.…”
Section: Related Workmentioning
confidence: 99%